Delírio de negação de Cotard. - Adrián Gramary; J M Romero; A Venâncio; Mário Moreira; Maria José Oliveira (Acta Médica Portuguesa, 2004)
The authors report a clinical case of a sixty-two-year-old woman admitted to hospital because Cotard's nihilistic delusion in a one year major depressive episode. The patient was treated with clomipramine and olanzapine with a rapid improvement and normalisation of humor and delusions.